Tight-binding model of the photosystem II reaction center: application to two-dimensional electronic spectroscopy - Andrius Gelzinis; Leonas Valkunas; Franklin D Fuller; Jennifer P Ogilvie; Shaul Mukamel; Darius Abramavicius (New Journal of Physics, 2013)
We propose an optimized tight-binding electron–hole model of the photosystem II (PSII) reaction center (RC). Our model incorporates two charge separation pathways and spatial correlations of both static disorder and fast fluctuations of energy levels. It captures the main experimental features observed in time-resolved two-dimensional (2D) optical spectra at 77 K: peak pattern, lineshapes and time traces. Analysis of 2D spectra kinetics reveals that specific regions of the 2D spectra of the PSII RC are sensitive to the charge transfer states. We find that the energy disorder of two peripheral chlorophylls is four times larger than the other RC pigments.